Observing Ocean Boundary Currents: Lessons Learned from Six Regions with Mature Observational and Modeling Systems - Ayoub, Nadia (2024)
Ocean boundary currents are complex and highly variable systems that play key roles in connecting the open and coastal ocean through cross-slope circulation and upwelling of nutrient-rich water. The structure, strength, and variability of boundary currents are associated with a broad range of spatial and temporal scales. For that reason, long-term boundary current monitoring is challenging and requires the use of complementary observing platforms and sensors coupled with numerical simulations. The Ocean Observations Physics and Climate Panel Boundary Systems Task Team recently held a virtual dialogue series to discuss six mature boundary current monitoring systems. The goal of the series was to examine strategies for developing a conceptual design for sustained observing activities applicable to a wide range of boundary current systems. This article provides a brief overview of the six systems, including users and the observational and modeling components needed to achieve scientific, operational, and societal goals. Ocean observing best practices and recommendations are shared to provide guidance for the coordination and sustainability of observing systems at ocean boundaries and to strengthen and integrate partnerships across and within the global observing networks.